Reference Gene Selection for Expression Analyses by qRT-PCR in Dendroctonus valens - Chunchun Zheng; Dongfang Zhao; Yabei Xu; Fengming Shi; Shixiang Zong; Jing Tao (Insects, 2020)
Dendroctonus valens is the main pest of the genus Pinus. To facilitate gene expression analyses, suitable reference genes for adults and mature larvae of D. valens under different temperature conditions were determined. In particular, we obtained the sequences of candidate reference genes, ACT, TUB, SHDA, PRS18, 18S rRNA, and CYP4G55, from transcriptome data. Real-time quantitative PCR was used to analyze gene expression, and geNorm, NormFinder, and BestKeeper were used to evaluate expression stability. Under different temperature conditions, the expression levels of 18S rRNA, PRS18, and TUB were stable in adults, in which 18S rRNA > PRS18 > TUB. In mature larvae, the expression levels of TUB, 18S rRNA, and SDHA were stable, in which TUB > 18S rRNA > SDHA. The combination of 18S rRNA and PRS18 is recommended for studies of gene expression in adults and the combination of 18S rRNA and TUB is effective for studies of gene expression in mature larvae of D. valens under different temperature conditions.